2021
DOI: 10.1016/j.bar.2019.100875
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the divide: The rise of the Indian Accountant from 1900 to 1932

Abstract: At its peak, the British Empire covered a quarter of the earth's land surface, had a population of 425 million of whom 366 million were non-white and, of these, 316 million lived in India (James 1998).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…For example, multiple studies in the Indian IT industry have found that a large majority of employees are from the Others, predominantly Brahmins, which some authors note is ''not surprising, given their monopoly over higher education and formal sector employment, especially in South India'' (e.g., Fernandez, 2017;Upadhya, 2007Upadhya, : 1864Shanker, 2000). A similar caste composition, i.e., high percentage of Others, predominantly Brahmins, was also reported for the early accounting profession in India (Sian & Verma, 2021).…”
Section: Implications Of Caste For Mnessupporting
confidence: 75%
“…For example, multiple studies in the Indian IT industry have found that a large majority of employees are from the Others, predominantly Brahmins, which some authors note is ''not surprising, given their monopoly over higher education and formal sector employment, especially in South India'' (e.g., Fernandez, 2017;Upadhya, 2007Upadhya, : 1864Shanker, 2000). A similar caste composition, i.e., high percentage of Others, predominantly Brahmins, was also reported for the early accounting profession in India (Sian & Verma, 2021).…”
Section: Implications Of Caste For Mnessupporting
confidence: 75%
“…Three key conceptions of accounting can be recognised: Accounting is technical practice, social practice and moral practice. Whilst, accounting is well-known universally as technical practice, Tsahuridu and Carnegie (2018) demonstrate how accounting has a much wider impact as social practice impacting on organisational and social activities and development. Accounting historians are shown to subscribe to this view, 'Far from treating accounting as technical practice, accounting historians are revealed as conceiving accounting as social practice, both impacting human behaviour and organisational and social functioning and development.…”
mentioning
confidence: 99%